PENERAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA INDUSTRI PERHOTELAN: STUDI KASUS PADA THE TANJUNG BENOA BEACH RESORT - Ni Kade Ayu Lisa Dwiyanti; Luh Putu Mahyuni (Jurnal Ilmiah Akuntansi & Bisnis, 2018)
The Implementation of Corporate Social Responsibility (CSR) in the Hospitality Industry: Case of the Tanjung Benoa Beach Resort. The purpose of this study is to investigate motivation for CSR, CSR practices, and the impact of CSR practices at the Tanjung Benoa Beach Resort Hotel. The type of data used was primary and secondary data. Data were collected using interviews and documentation. Qualitative analysis was applied to analyze the data. The results of this study are: 1) The Tanjung Benoa Beach Resort implements CSR to maintain harmonious relationship with the local society and to improve profit; 2) The types of CSR practices carried out at the Tanjung Benoa Beach Resort, namely: philanthropy-related CSR, environment-related CSR, CSR practices on education, CSR practices to employees; 3) The implementation of CSR at the Tanjung Benoa Beach Resort Hotel has positive impact in improving relationship with the local community, employees and in reducing operating costs, hence improve profit.Keywords: Motivation for CSR, CSR practices, the impact of CSR